Liderazgo del directivo y su incidencia en los resultados de la gestión administrativa de la Unidad Educativa San Pedro de Vilcabamba periodo lectivo 2022-2023 - González González, Rosa María (2023)
Leadership in the management staff is an aspect that significantly influences educational quality, since managers are responsible for conducting school management effectively and efficiently. Therefore, this research seeks to know the impact that the manager's leadership has on the administrative management results of the San Pedro de Vilcabamba Educational Unit for the 2022-2023 school year. To do this, it began with the formulation of the problem, where some relevant aspects are mentioned that are directed to the work of the rector and therefore to that of the management group of the institution under study. This research has been based on a mixed approach, where each of the variables was evaluated, placing emphasis on the process and development of managerial activities and identifying the different problems associated with aspects such as the management of administrative processes, disagreement in the designation of management positions and non-transparent results. Therefore, objectives were proposed, based on the theoretical and scientific investigation of the incidences of leadership in the educational field, identification of the administrative processes that develop good leadership in the San Pedro Vilcabamba Educational Unit, this research strongly highlights the relevance of the director's leadership in the results of administrative management in an educational institution. The results obtained indicate that competent leadership has the ability to enhance teacher performance, raise the quality of the teaching-learning process and improve management as a whole. However, in the specific context of the study, a lack of solid leadership and the implementation of effective administrative procedures is perceived, therefore, the promotion of a culture of shared leadership, the stimulation of professional development, the strengthening of communication are included. internal and the creation of collaborative environments. Keywords: Leadership; Executive staff; Administrative managemen